2004
DOI: 10.1002/ajmg.b.30027
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of a combined effect of SERTPR and TPH on SSRIs response in mood disorders

Abstract: We reported an independent association of the short variant of the serotonin transporter gene-linked polymorphic region (SERTPR) and tryptophan hydroxylase (TPH) genes with antidepressant response to selective serotonin reuptake inhibitors (SSRIs). The aim of the present study was to confirm the effect of the SERTPR and TPH gene variants on the SSRIs antidepressant activity in a new sample of major and bipolar depressives. Two hundred and twenty one inpatients (major depressives = 128, bipolar disorder = 93) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 35 publications
(38 reference statements)
2
40
0
Order By: Relevance
“…162 The short/long genotype was recently found to be associated with an odds ratio (OR) of 2.37 concerning adverse effects during treatment with SSRIs (dermatologic reactions, weight change and fatigue above all), and the homozygous short genotype showed an OR of 1.77. 163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes.…”
Section: Comtmentioning
confidence: 66%
“…162 The short/long genotype was recently found to be associated with an odds ratio (OR) of 2.37 concerning adverse effects during treatment with SSRIs (dermatologic reactions, weight change and fatigue above all), and the homozygous short genotype showed an OR of 1.77. 163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes.…”
Section: Comtmentioning
confidence: 66%
“…We believe our findings add relevant data for future metaanalyses helping to balance a conclusion towards a true association between the s/s genotype and unipolar depression particularly discounting the effect of comorbid GAD. Neurobiological evidence validating such true association between depression and the s/s genotype includes that the serotonin transporter is an important molecule targeted by most antidepressant drugs and potential functional or density changes in such a protein can influence both serotonergic pathways function and response to antidepressant therapy [Zanardi, 2001;Arias et al, 2003;Serretti, 2004]. Moreover, it has been suggested that variability at the 5-HTTLPR locus reduces the transcriptional efficiency of the gene, resulting in decreased SLC6A4 expression in the neuron .…”
Section: Discussionmentioning
confidence: 96%
“…Its short variant (s allele) reduces the transcriptional efficiency of the gene resulting in decreased serotonin transporter expression in the neuron . Independent studies have shown that individuals with s alleles tend to have a poorer response to selective serotonin re-uptake inhibitor (SSRI) antidepressant treatment [Zanardi, 2001;Arias et al, 2003;Serretti, 2004]. However, the assumption that expression of variants is associated with mental disorders or response to antidepressants has recently been questioned [Lim et al, 2006;Parsey, 2006].…”
Section: Introductionmentioning
confidence: 97%
“…Secondly, it could be that the effects of these polymorphisms are more easily seen when examining other phenotypes, where they may have a more direct effect, such as anxiety-related traits, neuroticism, personality [78][79][80] or response to antidepressant medication. [81][82][83] One argument to explain the weak association of the 5-HTT polymorphisms is antidepressantinduced mania (AIM). 84 According to this argument, bipolar patients who are homozygous for the low activity S allele of the 5-HTTLPR might be at a higher risk of developing a manic or hypo-manic episode after commencing antidepressant therapy.…”
Section: Discussionmentioning
confidence: 99%